1976
DOI: 10.1093/oxfordjournals.jhered.a108699
|View full text |Cite
|
Sign up to set email alerts
|

Staining technique for definite identification of individual cattle chromosomes in routine analysis

Abstract: The purpose of the present communication is to draw attention to the great applicability of a recently introduced R-banding technique for definite identification of cattle chromosomes in routine analysis. Banding patterns as well as densitometric measurements of normal bull chromosomes and the so-called 1/29 translocation are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Cattle cytogeneticists, in fact, know that quite exceptionally Q or G banding in this species can provide an unambigous banding pattern, especially· when contracted chromosome preparations are used, whereas the RBA technique, which involves acridine orange staining after late BrdU incorporation (DuTRILLAUX et al 1973) has been foud to give improved resolution and reliability. It is, therefore, to be preferred for the detailed description and definite identification of individual metaphase chromosomes of domestic animals (PoPEscu 1975;GusTAVSSON and HAGELTORN 1976;D1 BERARDINO et al 1981;D1 BERARDINO ~tnd IANNUZZI 1982). Since the Q or G banding pattern of chromosome 4 is very similar to that of chromosome 6 it is possible, in less than perfect preparations, to be misled in their identification.…”
Section: Methodsmentioning
confidence: 99%
“…Cattle cytogeneticists, in fact, know that quite exceptionally Q or G banding in this species can provide an unambigous banding pattern, especially· when contracted chromosome preparations are used, whereas the RBA technique, which involves acridine orange staining after late BrdU incorporation (DuTRILLAUX et al 1973) has been foud to give improved resolution and reliability. It is, therefore, to be preferred for the detailed description and definite identification of individual metaphase chromosomes of domestic animals (PoPEscu 1975;GusTAVSSON and HAGELTORN 1976;D1 BERARDINO et al 1981;D1 BERARDINO ~tnd IANNUZZI 1982). Since the Q or G banding pattern of chromosome 4 is very similar to that of chromosome 6 it is possible, in less than perfect preparations, to be misled in their identification.…”
Section: Methodsmentioning
confidence: 99%
“…Previous contributions on the RBA banding pattern in cattle chromosomes (Popescu, 1975;Gustavsson and Hagelthorn, 1976;De Giovanni et al, 1979;1988;Di Berardino et al, 1979, 1983, 1985a, 1985bDi Berardino and Iannuzzi, 1982) reported karyotypes which were based, as far as possible, on the Reading G-banded standard karyotype, but a direct correlation between G and R bands has not so far been reported. Recently, a G-and R-banding comparison of cattle prometaphase chromosomes arranged according to the Reading system has been reported (Iannuzzi, 1990) but without use of a sequential G-R banding procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Previous contributions on the RBA banding pattern in cattle chromosomes (Popescu, 1975;Gustavsson and Hagelthorn, 1976;De Giovanni et al, 1979;1988;Di Berardino et al, 1979, 1983, 1985a, 1985b (Iannuzzi, 1990) …”
Section: Discussionmentioning
confidence: 99%